(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In this article, the quality of fruits and vegetables is described in terms of food, taste and technological value. They depend on their chemical and mechanical composition, physical properties, external appearance and the ability not to lose these properties during storage. The quality of fruits and vegetables is affected by the type of product, agrotechnics, growing conditions, picking period, transportation equipment, types of containers, and storage methods. the above indicators also change depending on the storage period and conditions.